Thoughts on the Etyma for ‘corpse’ in Gyalrongic languages - Lai, Yunfan (2024)
This paper studies the four distinct native terms for ‘corpse’ attested in Gyalrongic languages. Through comparative analysis, it establishes the sound correspondences among cognates and proposes preliminary reconstructions. In a second step, it hypothesises on the origins of the etyma by examining potential cognates in other Sino-Tibetan languages. Two shared innovations can be found in the etyma for ‘corpse’. First, the Situ form *m-g[á]m is an innovated compound meaning ‘a person that is killed’; and second, the etymon *rə̆.quʶ is a shared innovation of Horpa and Tangut. By analysing the etymologies above, this paper aims to enhance our understanding of sound correspondences and changes within the Sino-Tibetan language family. Furthermore, it seeks to demonstrate the crucial role that etymological studies play in historical linguistics and language subgrouping. Despite their importance, such studies have not yet received sufficient attention from scholars specialising in Sino-Tibetan languages.